Endogenous Digoxin Like Immunoreactive Substances - Hakan BOZKAYA,; Hülya ÇETİNKAYA,; Yusuf UZUN,; Eralp TUTKAK,; Ali Reşit BEYLER,; Özden UZUNALİMOĞLU,; Abdülkadir DÖKMECİ, (Turkish Journal of Gastroenterology, 2020)
-